Review on current issue of clonal papaya (Carica papaya L.) for yield improvement / Nor Syazwani Mat Ghazi - Mat Ghazi, Nor Syazwani (Faculty of Plantation and Agrotechnology, 2017)
The papaya is rapidly in higher demand and become an important fruit in the international market as fresh and process product. The major problem in papaya cultivation is caused by the uneven in production and susceptible to pest and papaya ring spot virus (PVRS) disease. The cultivation gives rapid investment because of the early maturation and high production yield. Based on previous research the most prominent method in biotechnology and the conventional breeding can be superseded by micro propagation technique such as organogenesis and somatic embryogenesis with using the optimum protocol . The objectives of this review is to find out the best plant tissues culture and factor that effect yield of papaya. The application medium and supplement in tissue culture must be in optimum rate in regeneration explants.